Single Cell Biomedicine (Advances in Experimental Medicine and Biology, 2018)
The book focuses on various detection targets applied in single cell studies, including tumor tissue cells, circulating tumor cells (CTCs), disseminated tumor cells (DTCs), circulating tumor DNA (ctDNA), cell-free DNA (cfDNA) and cancer stem cells (CSCs). It also discusses and compares detection methods using these detection targets in different fields to reveal single cell biomedical functions. The volume focuses not only on the methods already been established and validated, and also the methods newly developed. The book also highlights the importance and potential of single cell biomedicine in the development and validation of precision medicine strategies. It is useful for researchers and students in the field of cell biology, molecular medicine and precision medicine etc.